Pengaruh Pelayanan, Fasilitas, dan Harga terhadap Keputusan Konsumen - Fauza El Azhar; Endang Triwidyati; Sudjiono; Budi Heryanto (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this research is to examine the impact of service, facilities, and price on consumer decisions at JP Motor Purwoasri Showroom in Kediri. The method used is quantitative, with data collection in the form of figures analyzed using systematic, objective, and measurable statistical techniques. The population in this study consists of all customers over one month, averaging around 500 individuals. Meanwhile, using a non-probability sampling method, a sample of 100 respondents was taken, followed by data collection through observation, interviews, questionnaire distribution, and literature review. Testing was conducted using validity tests, reliability, multiple linear regression, and the coefficient of determination (R²). The results of the data testing reveal that partially, there is a significant influence of service, facilities, and price on consumer decisions (sig. < 0.05). Collectively, all three also have a significant influence based on the F test (sig. 0.002 < 0.05).